Microworm Culture for Use in Freshwater Ornamental Aquaculture - Shane Ramee; Taylor Lipscomb; Matthew DiMaggio (EDIS)
A small nematode worm commonly referred to as a “microworm”, has been a staple live feed used in the ornamental aquaculture industry for over 50 years. These worms are small enough to be ingested by the larvae of many commonly cultured ornamental species and their production methods are simple and reliable. Microworms have the potential to provide appropriate nutrition in a live feed organism that is cultured entirely in house and involves less labor and cost than newly hatched Artemia. In this article, the biology, environmental requirements, and culture techniques for microworms are discussed as well as their importance for the larval culture of freshwater fish species.